Peran Financial Constraint dalam Memoderasi Pengaruh Struktur Modal Terhadap Nilai Perusahaan - Sari, Murni (Universitas Muhammadiyah Metro, 2022)
This study aims to improve the relationship between capital structure and firm value using financial constraints on cash holdings as a moderating variable for mining companies and metal manufacturing companies 2016-2020. The sample selection technique used the purposive sampling technique so that a sample of 26 companies was obtained. The data analysis method was analyzed using multiple linear regression analysis using the SPSS version 23.0 for windows application. Based on the results of the study partially capital structure has a positive and significant effect on firm value, capital structure has a positive and significant effect on firm value. The control variable company size has a positive effect on firm value, operating cash flow has no significant effect on firm value, and intangible assets have no significant effect on firm value. financial constraints on cash holdings cannot moderate the relationship between capital structure and firm value. independent variables together can explain the dependent variable. Based on the research results, firm value can be increased by increasing debt or increasing the capital structure ratio. Improved capital structure must pay attention to the balance between benefits and costs arising from debt